Znaczenie alergii na białka mleka krowiego w kolce niemowlęcej - Krogulska, Aneta; Popielarz, Maria (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Infantile colic is a common problem in infancy. Healthy infant before the age of 5 months, in which repeated episodes of long-lasting crying or irritability, without a fixed cause and without the possibility of their detention or prevention fulfil the criteria for diagnosis of infantile colic. Although the pathogenesis of colic is unknown, it takes into account: biopsychosocial mechanism, motility disorders, lactose intolerance, intestinal dysbiosis, behavioral factors and cow’s milk protein allergy (CMPA). The relationship between colic and CMPA may result from combined dysfunctions associated with peristalsis, microbiota and enteric nervous system (ENS). Motility disorders caused by increased production of inflammatory cytokines (in allergy) lead to abnormal peristalsis, registered as pathological stimuli in the shape of colic. Dysbiosis in CMPA also influences the motility and gas production, resulting in the development of colic symptoms. ENS is based on the intestinal microbiota and central nervous system. The development of inflammation (CMPA) activates ENS and abnormal motility, causing colic. Universal methods of management in colic are still missing. In every case, the organic causes of complaints should be excluded. The principal method of treatment is to educate and reassure parents. The beneficial effect is possible to achieve through the implementation of appropriate dietary management using: comfort formula, hypoallergenic diet at a nursing mother, extensively hydrolyzed or amino acid formulas. Therapeutic options are also the probiotics and lactase. If no signs of improvement are observed, hospitalization should be considered. Despite the probable common pathogenesis colic and CMPA, it lacks objective studies documenting their interdependence and the actual results are ambiguous.